2005
DOI: 10.4049/jimmunol.175.7.4180
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Direct Suppression of B Cells by CD4+CD25+ Regulatory T Cells

Abstract: Regulatory T cells (Tregs) can potentially migrate to the B cell areas of secondary lymphoid tissues and suppress T cell-dependent B cell Ig response. T cell-dependent Ig response requires B cell stimulation by Th cells. It has been unknown whether Tregs can directly suppress B cells or whether they must suppress Th cells to suppress B cell response. We report here that Foxp3+ Tregs are found in T-B area borders and within germinal centers of human lymphoid tissues and can directly suppress B cell Ig response.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
418
1
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 517 publications
(444 citation statements)
references
References 24 publications
19
418
1
6
Order By: Relevance
“…37 Lim et al also recently demonstrated that regulatory T cells can suppress B-celldependent immunoglobulin production and class switch recombination in the absence of T-helper cells. 38 However, the mechanism for the suppression remains unclear in these studies. We examined the direct effect of CD4 ϩ CD25 ϩ T cells on B cells and found that, when restimulated with either anti-CD3 or antigen, preactivated CD4 ϩ CD25 ϩ T cells mediated apoptosis of activated B cells by a cytotoxic granule-mediated mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…37 Lim et al also recently demonstrated that regulatory T cells can suppress B-celldependent immunoglobulin production and class switch recombination in the absence of T-helper cells. 38 However, the mechanism for the suppression remains unclear in these studies. We examined the direct effect of CD4 ϩ CD25 ϩ T cells on B cells and found that, when restimulated with either anti-CD3 or antigen, preactivated CD4 ϩ CD25 ϩ T cells mediated apoptosis of activated B cells by a cytotoxic granule-mediated mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…Decreased number and function of FOXP3 + Treg have also been described in the plasma cell-derived malignancy multiple myeloma [37] and in Sezary syndrome, the aggressive leukaemic variant of cutaneous T cell lymphoma [27,38]. Since Treg can suppress B as well as T cell function [39,40], the expansion of such tumours may be slowed by Treg. Therefore, immunotherapeutic strategies aiming to reduce Treg numbers, to improve the efficacy of cancer vaccines in haematological malignancies, may need to carefully balance advantages gained by improving T cell responses to tumour antigens with possible disadvantages arising from removing direct Treg suppression of the malignant population.…”
Section: Manipulation Of Treg For Cancer Therapymentioning
confidence: 99%
“…CD4 1 CD25 1 ab T cells are well known for their ability to control the activity of several immune cell populations in vitro and in vivo, including effector CD4 1 CD25 À and CD8 1 ab T cells [13], NK [14] and NKT cells [15], B cells [16], DC [17], and monocytes/macrophages [18]. As a result, CD4 1 CD25 1 ab T cells, and particularly those that develop in the thymus through a Foxp3-dependent genetic program [19,20], so-called ''naturally occurring'' Treg (nTreg), are pivotal to maintaining immune homeostasis and preventing inflammatory and autoimmune diseases [21].…”
Section: Introductionmentioning
confidence: 99%